2021
DOI: 10.1039/d1ra00809a
|View full text |Cite
|
Sign up to set email alerts
|

Facile construction of a family of supramolecular gels with good levofloxacin hydrochloride loading capacity

Abstract: A family of low molecular weight gelators with different alkyl chain lengths was constructed, having excellent gelation ability and antibiotic loading capacity. A low molecular weight hydrogelator was obtained by adjusting the length of alkyl chain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 53 publications
0
6
0
Order By: Relevance
“…18 We have pointed out that, during a sol-to-gel transition, the micellar aggregates can direct the gel properties. 19 Furthermore, changing hydrophobicity is reported to influence gelation kinetics, 20 morphology and thermal behaviour, 21 mechanical properties, 22 self-healing, 23 and catalytic activity 24 of single component systems. The hydrophobic microenvironments within the fibre network of hydrogels have also been found to enhance stability of encapsulated materials like enzymes and proteins.…”
Section: Varying the Hydrophobic Spacer To Influence Multicomponent Gelationmentioning
confidence: 99%
“…18 We have pointed out that, during a sol-to-gel transition, the micellar aggregates can direct the gel properties. 19 Furthermore, changing hydrophobicity is reported to influence gelation kinetics, 20 morphology and thermal behaviour, 21 mechanical properties, 22 self-healing, 23 and catalytic activity 24 of single component systems. The hydrophobic microenvironments within the fibre network of hydrogels have also been found to enhance stability of encapsulated materials like enzymes and proteins.…”
Section: Varying the Hydrophobic Spacer To Influence Multicomponent Gelationmentioning
confidence: 99%
“…Compared to the spectrum of the gelator, the frequency of the carbonyl-stretching vibration peak of xerogel also slightly shifted from a low wavenumber (from 1641.6 cm −1 (gelator) to 1640.8 cm −1 (25 mg/mL)), while the frequency of the N–H deformation vibration peak of xerogel appeared at a high wavenumber (1536.6 cm −1 (10 mg/mL), 1537.2 cm −1 (25 mg/mL)). The results indicated that the hydrogen bond formed between carbonyl and the N–H bond [ 38 ]. The spectral band of the methylene-stretching vibration peak in xerogel was stronger than in gelator, which indicated that the alkyl chains between gelators in the gel phase are stacked, and that Van der Waals forces exist between alkyl chains.…”
Section: Resultsmentioning
confidence: 99%
“…Hydrazide and its derivatives have received more attention in the field of drug research and development in recent years due to their biological activities (antibacterial and anti-inflammatory) [ 35 , 36 , 37 ]. Due to hydrazide’s strong hydrophilicity and multiple hydrogen-bonding sites, hydrazide groups are widely used as building blocks to regulate the hydrophilicity and hydrophobicity balance of compounds to construct supramolecular hydrogels [ 38 , 39 , 40 ]. Smith et al developed a supramolecular hydrogel based on the hydrazide compound, which can react with aldehydes without disrupting the gel network and selectively reacted with specific aldehydes in aldehyde mixtures [ 41 ].…”
Section: Introductionmentioning
confidence: 99%
“…The different release phenomena could be explained by the different properties of the drugs. LVX is a water-soluble compound that can easily dissolve and enter the release medium by free diffusion, thereby presenting a more complete release after 3 days [60]. However, AMB is practically insoluble in water at neutral pH values.…”
Section: Release Of Topical Filmsmentioning
confidence: 99%